Can galaxy clusters, type Ia supernovae, and the cosmic microwave background rule out a class of modified gravity theories? - Holanda, R. F.L.; Pereira, S. H. [UNESP] (American Physical Society (APS), 2016)
In this paper we study cosmological signatures of modified gravity theories that can be written as a coupling between an extra scalar field and the electromagnetic part of the usual Lagrangian for the matter fields. In these frameworks, the electromagnetic sector of the theory is affected and variations of fundamental constants, of the cosmic distance-duality relation and of the evolution law of the cosmic microwave background (CMB) radiation, are expected and are related to each other. In order to search these variations we perform jointly analyses with angular diameter distances of galaxy clusters, luminosity distances of type Ia supernovae, and TCMB(z) measurements. We obtain tight constraints with no significant indication of violation of the standard framework.